Olfactory cognition : from perception and memory to environmental odours and neuroscience - Zucco, Gesualdo; Herz, Rachel, 1963-; Schaal, Benoist (Advances in consciousness research ;, 2012)
This book was conceived as a tribute to one of the founders of the psychological study of the sense of smell, Professor Trygg Engen. The book is divided into four sections. The first reunites the fields of psychophysics and the perception of environmental odours and discusses the impact of odours on beliefs and expectations. The second addresses cognitive processes in olfaction, how odours are interpreted, lexicalized, associated with contexts and remembered. The third focuses on the cerebral bases of olfactory awareness and the neuropsychological investigation of olfaction with special emphas.